2018
DOI: 10.1093/chemse/bjy025
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory fMRI: Implications of Stimulation Length and Repetition Time

Abstract: Studying olfaction with functional magnetic resonance imaging (fMRI) poses various methodological challenges. This study aimed to investigate the effects of stimulation length and repetition time (TR) on the activation pattern of 4 olfactory brain regions: the anterior and the posterior piriform cortex, the orbitofrontal cortex, and the insula. Twenty-two healthy participants with normal olfaction were examined with fMRI, with 2 stimulation lengths (6 s and 15 s) and 2 TRs (0.901 s and 1.34 s). Data were analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 57 publications
1
27
0
Order By: Relevance
“…Respiration-triggered event-related fMRI designs are proven to yield a stronger activation of the olfactory cortex compared to fixed-timing odor delivery (Wang et al, 2017). Nevertheless, we chose a less complex experimental design with fixed-timing odor delivery, which was previously validated in healthy participants (Georgiopoulos et al, 2018). The lack of significant differences between the two groups in the activation of olfactory cortex, when analyzed with the GLM, could be partially attributed to the fixed-timing odor delivery; a combination with visual cuing prior to odor presentation could potentially be beneficial in future studies (Moessnang et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Respiration-triggered event-related fMRI designs are proven to yield a stronger activation of the olfactory cortex compared to fixed-timing odor delivery (Wang et al, 2017). Nevertheless, we chose a less complex experimental design with fixed-timing odor delivery, which was previously validated in healthy participants (Georgiopoulos et al, 2018). The lack of significant differences between the two groups in the activation of olfactory cortex, when analyzed with the GLM, could be partially attributed to the fixed-timing odor delivery; a combination with visual cuing prior to odor presentation could potentially be beneficial in future studies (Moessnang et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Establishing a robust and reliable fMRI design is of high importance for the investigation of neural activity within the olfactory network. Our research group has previously studied the effects of stimulation length and MRI acquisition repetition time (TR) in the activation pattern of the olfactory cortex in healthy subjects, concluding that short stimulation length and short TR should be preferred in order to achieve maximum signal increase and short time to peak signal change (Georgiopoulos et al, 2018). In the present study, our previous methodological findings are applied in PD in order to elucidate potentially altered activation patterns and functional connectivity within olfactory brain areas.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study (5) suggested a benefit of a high number of repetitions and short stimulation duration due to oscillations in the neural signal, which only occur after longer duration. Our study partly supports this assumption, as the combination of short and continuous stimulation with higher number of repetitions showed strongest activations.…”
Section: Discussionmentioning
confidence: 99%
“…Besides that, the rapid adaptation to olfactory stimuli needs to be considered (1) and the length of the olfactory stimulation period as neural oscillations occurring after a longer stimulation time may affect the signal (5).…”
Section: Introductionmentioning
confidence: 99%
“…It has been argued that in addition to a short task duration, the stimulation within runs (eg, in each block) is also important for a consistent activation across the primary (piriform) and secondary olfactory areas . For example, a fast repetition time (TR < 1 second) combined with a short stimulation length (6‐second odor stimulation in a 20‐second block) was associated with more rapid increase of BOLD signal in the olfactory regions . A short total odor exposure time may prevent rapid adaptation in the primary olfactory areas .…”
Section: Discussionmentioning
confidence: 99%